Aktivitas Antidiabetes Kulit Batang Arcangelisia flava dari Sulawesi Tenggara, Indonesia Secara In Vivo Terintegrasi dengan Analisis Farmakologi Jaringan (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
The Arcangelisia flava plant has previously been reported to reduce blood glucose levels in experimental animals. However, there have been no reports on the antidiabetic activity of its stem bark. This study aimed to evaluate the antidiabetic activity of A. flava extracts and fractions, identify their bioactive compounds, and explore the mechanistic pathways involved using the network pharmacology approach. The chemical constituents of the n-hexane fraction were analyzed using gas chromatography mass spectrometry (GC-MS). The in vivo antidiabetic test was conducted on Mus musculus induced with streptozotocin/niacinamide. Blood glucose levels were measured using the oral glucose tolerance test (OGTT) The antioxidant activity of the extracts and fractions was determined using the ABTS assay. The result showed that the GC-MS analysis of the n-hexane fraction identified 18 compounds belonging to seven chemical groups, namely aromatic hydrocarbons, ketones and alcohols, phenolic aldehydes, sulfur compounds, terpenes, fatty acid derivatives, and alkaloids. The highest percentage of blood glucose reduction was observed in the group treated with ethanolic extract 500 mg/kg BW (50.25%), followed by glibenclamide (43.53%), ethyl acetate fraction 125 mg/kg BW (42.82%), ethanolic extract 250 mg/kg BW (41.88%), n-hexane fraction 125 mg/kg BW (34.96%), butanol fraction 125 mg/kg BW (34.28%), and ethanolic extract 125 mg/kg BW (34.14%), respectively. The ABTS assay produced IC₅₀ values for vitamin C, ethanolic extract, n-hexane fraction, ethyl acetate fraction, and butanol fraction of 8.00, 49.80, 110.25, 10.20, and 18.44 µg/mL, respectively. Network pharmacology analysis of compound 7 and compound 17 from the n-hexane fraction revealed antidiabetic potential through inhibition of the AGE–RAGE signaling pathway in diabetic complications. The key target proteins involved included MAPK1, MMP2, MAPK14, MAPK3, PIK3CA, and TGFBR1. In conclusion, the extracts and fractions of Arcangelisia flava exhibit strong potential as antidiabetic and antioxidant agents. The n-hexane fraction, in particular, is presumed to exert its antidiabetic activity through inhibition of the AGE–RAGE signaling pathway, which plays a critical role in diabetic complications.